Dermis-fat graft for anophthalmic socket reconstruction: indications and outcomes - Galindo-Ferreiro, Alicia; Khandekar, Rajiv; Al Hassan, Sultan; Al-Hammad, Fatimah; Al-Subaie, Hamad; Schellini, Silvana Artioli [UNESP] (Consel Brasil Oftalmologia, 2018)
Purpose: To evaluate the outcomes of dermis-fat graft procedure for orbital volume replacement in anophthalmic socket. Methods: A retrospective chart review was performed studying all dermis-fat graft surgeries done at King Khlaed Eye Specialist Hospital in the last 10-year period. Sixty-two anophthalmic socket carriers underwent dermis-fat graft during the study period. Data were collected on characteristics of the patients, postoperative complications, cosmesis, and functional results such as the ability to hold an external prosthesis. Results: Mean age of the patients included in the study was 34.2 +/- 9.7 years. There were 38.7% of patients with grade 3 anophthalmic socket, 64.5% of patients had an acquired anophthalmic socket, and dermis-fat graft was performed as a secondary procedure in 61.3% of patients. Postoperative complications included lagophthalmos (22.6%), graft necrosis (17.7%), pyogenic granuloma (12.9%), decreased graft size (12.9%), malpositioned lids (3.2%), and volume deficiency (3.2%). The prosthesis was held in place in 49 patients (79%) preoperatively and in 55 patients (88.7%) postoperatively. Conclusion: Dermis-fat graft is an excellent option for congenital or acquired as well as primary or secondary anophthalmic sockets, with or without contraction. The outcomes are favorable, and complications are rare.
Keywords: Anophthalmos/surgery; Orbit; Dermis; Adipose tissue/transplantation; Retrospective study